2016
DOI: 10.3892/mmr.2016.6014
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of endoplasmic reticulum stress is associated with diaphragm contractile dysfunction in a rat model of sepsis

Abstract: Sepsis often causes diaphragm contractile dysfunction. Endoplasmic reticulum (ER) stress has been implicated in muscle contractile dysfunction. However, it remains unknown if ER stress occurs in the diaphragm during sepsis. In the present study, rats were divided into 4 groups and received placebo or one of three durations of endotoxin treatment (24, 48 h and 7 days). Isometric contractile force of the diaphragm was measured and lung wet-to-dry ratio (W/D) was calculated. Hematoxylin and eosin (H&E) staining o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 53 publications
4
21
0
1
Order By: Relevance
“…Several reports demonstrate that ER stress and unfolded protein response (UPR) pathway get activated under various muscle conditions such exercise [41], aging[42], cancer cachexia[43], sepsis[44] and myopathy[45]. ER stress-induced UPR suggests to play an important role in maintaining skeletal muscle mass and function.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrate that ER stress and unfolded protein response (UPR) pathway get activated under various muscle conditions such exercise [41], aging[42], cancer cachexia[43], sepsis[44] and myopathy[45]. ER stress-induced UPR suggests to play an important role in maintaining skeletal muscle mass and function.…”
Section: Discussionmentioning
confidence: 99%
“…Although ER stress and activation of the UPR have been observed in skeletal muscle in multiple atrophying conditions, their exact role in the regulation of skeletal muscle mass remains poorly understood. ER stress has been implicated in diaphragm contractile dysfunction in a mouse model of sepsis [93]. A previous study found no changes in the levels of GRP78, calreticulin, CHOP, vinculin, the type I D-myo-inositol 1,4,5-trisphosphate receptor, protein kinase R, and eIF2a in skeletal muscle upon hind limb unloading, a model of disuse atrophy [94].…”
Section: Atrophymentioning
confidence: 98%
“…Under ER stress, unfolded protein response sensors might switch their signals to stimulate the cell death by unique registration signaling mechanisms, which include several steps: the first is transcriptional activation of the CEBP homologous protein (CHOP) gene, mediated by PKR-like endoplasmic reticulum kinase (PERK), inositol-requiring enzyme 1 (IRE1), and activating transcription factor 6 (ATF6); the activation of the JNK pathway, mediated by IRE, followed by the subsequent activation of TNF receptor-associated factor 2 and apoptotic signal-regulated kinase 1; finally, the activation of caspase-12 associated and the activated caspase-12 migrates from the ER to the cytosol and then cleaves caspase-9, and finally activates caspase-3 [77,78,79]. In sepsis animal models, markers of increased ER stress (such as glucose-regulated protein 94 (GRP94), CHOP, and caspase-12) are detected in several organs including the heart and liver, as well as these markers are directly connected with the extent of organ dysfunction, which may be a major cause for sepsis-induced multiple organ failure [80]. ER stress brings about abnormal apoptosis in sepsis animals, suggesting that ER stress-mediated apoptosis represents a potential new target for clinical prevention and treatment for sepsis.…”
Section: Pathogenesis Of Sepsismentioning
confidence: 99%